The Effect of Using The Picture and Picture Learning Model Assisted by The Pancasila Board On The Learning Outcomes of Pancasila Education In Grade 4 Elementary School - Septiani Putri Kinanti; Zulfadewina Zulfadewina (Dinasti Publisher, 2024)
Pancasila Education is still perceived as tedious and challenging. Based on the findings of these observations, it is evident that students' level of interest in Pancasila Education subjects remains relatively low. The teaching and learning process of Pancasila material sometimes relies solely on textbooks and the lecture approach, resulting in suboptimal classroom outcomes. This study employs quantitative methodologies. The objective of this study is to investigate if the utilization of Pancasila Board media in Pancasila Education has an impact on the learning outcomes of fourth-grade students. This study used a quasi-experimental research method known as the Quasi Experimental Design, specifically utilizing the